Antioxidant effects of carnitine supplementation on 14-3-3 protein isoforms in the aged rat hippocampus detected using fully automated two-dimensional chip gel electrophoresis. (December 2014) - Iwamoto, M.; Miura, Y.; Tsumoto, H.; Tanaka, Y.; Morisawa, H.; Endo, T.; Toda, T.
Abstract We here described the antioxidant effects of carnitine supplementation on 14-3-3 protein isoforms in the aged rat hippocampus detected using the fully automated two-dimensional chip gel electrophoresis system (Auto2D). This system was easy and convenient to use, and the resolution obtained was more sensitive and higher than that of conventional two-dimensional polyacrylamide gel electrophoresis (2-D PAGE). We separated and identified five isoforms of the 14-3-3 protein (beta/alpha, gamma, epsilon, zeta/delta, and eta) using the Auto2D system. We then examined the antioxidant effects of carnitine supplementation on the protein profiles of the cytosolic fraction in the aged rat hippocampus, demonstrating that carnitine supplementation suppressed the oxidation of methionine residues in these isoforms. Since methionine residues are easily oxidized to methionine sulfoxide, the convenient and high-resolution 2-D PAGE system can be available to analyze methionine oxidation avoiding artifactual oxidation. We showed here that the Auto2D system was a very useful tool for studying antioxidant effects through proteomic analysis of protein oxidation.